2019
DOI: 10.1002/pi.5767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoparticle localization on the rheology, morphology and toughness of nanocomposites based on poly(lactic acid)/natural rubber/nanosilica

Abstract: In this study, poly(lactic acid)/natural rubber blends and their nanocomposites with silica nanoparticles were prepared via the melt mixing process. The rheology, morphology and impact resistance of the prepared samples were examined depending on the silica content (0–7 phr) and its localization. The results obtained showed that the incorporation of silica below its percolation threshold led to its selective localization in the matrix and mostly near the interface. This was in agreement with the results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…As can be seen, the PCL domain size decreased upon the addition of SFNP, which demonstrates the compatibilizing effect of nanoparticle. A similar result also was reported by Nematollahi et al [41], who revealed that the use of nanosilica in the PLA/natural rubber (PLA/NR) blends caused a reduction of the NR droplet sizes. These results indicate that nanoparticle can promote the compatibility between the PLA matrix and dispersed phases.…”
Section: Thermal Characterizationsupporting
confidence: 88%
“…As can be seen, the PCL domain size decreased upon the addition of SFNP, which demonstrates the compatibilizing effect of nanoparticle. A similar result also was reported by Nematollahi et al [41], who revealed that the use of nanosilica in the PLA/natural rubber (PLA/NR) blends caused a reduction of the NR droplet sizes. These results indicate that nanoparticle can promote the compatibility between the PLA matrix and dispersed phases.…”
Section: Thermal Characterizationsupporting
confidence: 88%
“…It is worth noting that the blending of synthetic polymers with PLA reduces the bio‐based attribute of PLA. Natural rubber (NR), a well‐known and renewable resource rubber derived from the latex of Hevea brasiliensis trees, is used as a green elastomer . However, the biodegradability of NR is still an environmental concern, but due to its high flexibility, biocompatibility and low cost, has been used by various researchers to enhance the toughness of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the previous research, Nematollahi et al 26 reported that the elongation at break of PLA was increased by 15‐fold (~72%) with the addition of only 10 wt.% NR through the melt mixing process. Moreover, their investigation showed that the influence of rubber on the flexibility of PLA increased in the presence of epoxidized natural rubber (ENR).…”
Section: Introductionmentioning
confidence: 89%